NF546 [4,4′-(Carbonylbis(imino-3,1-phenylene-carbonylimino-3,1-(4-methyl-phenylene)-carbonylimino))-bis(1,3-xylene-α,α′-diphosphonic Acid) Tetrasodium Salt] Is a Non-Nucleotide P2Y11 Agonist and Stimulates Release of Interleukin-8 from Human Monocyte-Derived Dendritic Cells - Meis, Sabine; Hamacher, Alexandra; Hongwiset, Darunee; Marzian, Claudia; Wiese, Michael; Eckstein, Niels; Royer, Hans-Dieter; Communi, Didier; Boeynaems, Jean-Marie; Hausmann, Ralf; Schmalzing, Günther; Kassack, Matthias U. (The Journal of pharmacology and experimental therapeutics, 2010)
The G protein-coupled P2Y11 receptor is involved in immune system modulation. In-depth physiological evaluation is hampered, however, by a lack of selective and potent ligands. By screening a library of sulfonic and phosphonic acid derivatives at P2Y11 receptors recombinantly expressed in human 1321N1 astrocytoma cells (calcium and cAMP assays), the selective non-nucleotide P2Y11 agonist NF546 [4,4′-(carbonylbis(imino-3,1-phenylene-carbonylimino-3,1-(4-methyl-phenylene)carbonylimino))-bis(1,3-xylene-α,α′-diphosphonic acid) tetrasodium salt] was identified. NF546 had a pEC50 of 6.27 and is relatively selective for P2Y11 over P2Y1, P2Y2, P2Y4, P2Y6, P2Y12, P2X1, P2X2, and P2X2-X3. Adenosine-5′-O-(3-thio)triphosphate (ATPγS), a nonhydrolyzable analog of the physiological P2Y11 agonist ATP, and NF546 use a common binding site as suggested by molecular modeling studies and their competitive behavior toward the nanomolar potency antagonist NF340 [4,4′-(carbonylbis(imino-3,1-(4-methyl-phenylene)carbonylimino))bis(naphthalene-2,6-disulfonic acid) tetrasodium salt] in Schild analysis. The pA2 of NF340 was 8.02 against ATPγS and 8.04 against NF546 (calcium assays). NF546 was further tested for P2Y11-mediated effects in monocyte-derived dendritic cells. Similarly to ATPγS, NF546 led to thrombospondin-1 secretion and inhibition of lipopolysaccharide-stimulated interleukin-12 release, whereas NF340 inhibited these effects. Further, for the first time, it was shown that ATPγS or NF546 stimulation promotes interleukin 8 (IL-8) release from dendritic cells, which could be inhibited by NF340. In conclusion, we have described the first selective, non-nucleotide agonist NF546 for P2Y11 receptors in both recombinant and physiological expression systems and could show a P2Y11-stimulated IL-8 release, further supporting the immunomodulatory role of P2Y11 receptors.